Islamic Political Social Values in Society - Dianto Dianto (Proceeding International Seminar of Islamic Studies, 2019)
Social life in the community becomes the most important thing to be applied by all humans. By having social in him, he can become a good person. But what is happening at this time is that many people who live do not have social in themselves so that he becomes an arrogant human being and has no value to the benefits of those around him. Social attitudes can be had in various ways that can make themselves more noble before God or humans. Today we want to see the extent to which social attitudes can be had for those who are active in the politics of education.This means that politics can bring the good of humans themselves if used in a good way. But on the contrary social values cannot be possessed properly if one uses politics. Islam currently faces a paradox which is a reality that cannot be denied. In the past, Muslims experienced victory, practically without other forces that surpassed it, so that the attitude of the Muslims at that time was the attitude of a winning group, superior invincible, free from fear, and never worried about other groups. In social and political dynamics, it turns out that it does not necessarily make Islamic politics easily to win the struggle in the spatial and legal dimensions in Indonesia today.We can understand together that politics must be closely related to power, while power itself is one of the things that are most in demand by humans. It seems no exaggeration to say that the study of this field in its various dimensions always becomes interesting. By looking at the problems that occur in educational politics, we can see social and political dynamics, apparently not necessarily making Islamic politics easily to win the struggle in the spatial and legal dimensions in Indonesia today.